Model Komunikasi dan Informasi Terpadu dalam Menanamkan Moderasi Beragama di Bali - I Nyoman Alit Putrawan (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2022)
The purpose of this research is to analyze how the communication and information model is implemented to integrate religion in Bali. By using the document analysis method, the results of the research show that Bali is recognized as multiculturalism with a religious belief. Both keep human society and peddle it alive through mutual interaction; promote mediation and through effective conflict resolution. Communication and religion facilitate Pakistan in the etiquette of human behavior through mutual sharing, experimentation, and intellectual stimulation. It should be noted that both cross-religious communication has been very abusive and that of modern human society. So that there is a need for encouragement from local religious leaders to communicate effectively and positively for the betterment of their community. On the other hand, the supervisor should not underestimate religion, but be very and sincere in his beliefs and enforce constitutional recognition in terms of empowerment and participation. This will be very important community integration. In this way, people and society will be able to maintain close contact among their own peacocks more effectively and productively.